2015
DOI: 10.1001/jamainternmed.2015.3871
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden Among Patients Who Were Hospitalized for Heart Failure

Abstract: guidelines for the diagnosis and treatment of asymptomatic bacteriuria in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…One study showed that symptoms in patients with HF that were recognized at the start of a hospitalization were often not improved at discharge. (180) The consequences of uncontrolled symptoms while hospitalized is especially problematic for pain, as the level of pain during hospitalization is strongly associated with increased levels of pain following discharge home. (181) When symptom management is challenging, collaboration with palliative care for expert symptom management can benefit the patient.…”
Section: Collaborative Management and A Call To Actionmentioning
confidence: 99%
“…One study showed that symptoms in patients with HF that were recognized at the start of a hospitalization were often not improved at discharge. (180) The consequences of uncontrolled symptoms while hospitalized is especially problematic for pain, as the level of pain during hospitalization is strongly associated with increased levels of pain following discharge home. (181) When symptom management is challenging, collaboration with palliative care for expert symptom management can benefit the patient.…”
Section: Collaborative Management and A Call To Actionmentioning
confidence: 99%
“…28 With the need for intensive symptom management for ESHF patients, incorporation of the PC approach in transitional care support may be beneficial to patients upon hospital discharge. 29 Home PC not only saves costs but can also increase patient satisfaction 30 and improve QOL 31 and caregiver distress. 32 Evidence of the effects of home PC in reducing the symptom burden, particularly for cancer patients, but not caregiver grief was reported in a recent Cochrane review.…”
Section: Introductionmentioning
confidence: 99%
“…These symptoms are regularly present, even after a hospitalization, when more than 40 % of patients report no improvement in dyspnea, anxiety, fatigue, and pain [9]. Major clinical guidelines recommend the inclusion of symptom monitoring as part of routine self-care management of patients with heart failure [10].…”
Section: Introductionmentioning
confidence: 99%